Microbial interaction with and tolerance of radionuclides: underlying mechanisms and biotechnological applications. Issue 3 (8th December 2020) - Lopez‐Fernandez, Margarita; Jroundi, Fadwa; Ruiz‐Fresneda, Miguel A.; Merroun, Mohamed L.
Summary: Radionuclides (RNs) generated by nuclear and civil industries are released in natural ecosystems and may have a hazardous impact on human health and the environment. RN‐polluted environments harbour different microbial species that become highly tolerant of these elements through mechanisms including biosorption, biotransformation, biomineralization and intracellular accumulation. Such microbial–RN interaction processes hold biotechnological potential for the design of bioremediation strategies to deal with several contamination problems. This paper, with its multidisciplinary approach, provides a state‐of‐the‐art review of most research endeavours aimed to elucidate how microbes deal with radionuclides and how they tolerate ionizing radiations. In addition, the most recent findings related to new biotechnological applications of microbes in the bioremediation of radionuclides and in the long‐term disposal of nuclear wastes are described and discussed. Abstract : Radionuclide polluted environments harbor microbial species highly tolerant to these elements through mechanisms like biosorption, biotransformation, biomineralization and intracellular accumulation. The microbial‐ radionuclide interaction processes have a great potential for biotechnological applications. This review provides the state‐ of‐ the‐ art of all aspects of these investigations.